2019
DOI: 10.1038/s41598-019-47373-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Monoacylglycerol Derivatives from Indonesian Edible Oil and Their Antimicrobial Assay against Staphylococcus aureus and Escherichia coli

Abstract: In the present work, linoleic acid and oleic acid were isolated from Indonesian corn oil and palm oil and they were used to prepare monoacylglycerol derivatives as the antibacterial agent. Indonesian corn oil contains 57.74% linoleic acid, 19.88% palmitic acid, 11.84% oleic acid and 3.02% stearic acid. While Indonesian palm oil contains 44.72% oleic acid, 39.28% palmitic acid, 4.56% stearic acid and 1.54% myristic acid. The oleic acid was purified by using Urea Inclusion Complex (UIC) method and its purity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 33 publications
0
22
0
3
Order By: Relevance
“…The presence of hydroxyl groups on the glycosyl part of the esters allows them to interact with the gram-positive bacterial cell wall. Once the compounds interact with the cell wall through intermolecular interaction, such as hydrogen bonding and van der Waals interaction, the cell will be destabilized, which can lead to bacteria lysis [28,29,30]. However, the prepared compounds also showed weak antibacterial activity to the gram-negative bacteria, perhaps due to the presence of the hydrophobic alkyl chain of the esters.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of hydroxyl groups on the glycosyl part of the esters allows them to interact with the gram-positive bacterial cell wall. Once the compounds interact with the cell wall through intermolecular interaction, such as hydrogen bonding and van der Waals interaction, the cell will be destabilized, which can lead to bacteria lysis [28,29,30]. However, the prepared compounds also showed weak antibacterial activity to the gram-negative bacteria, perhaps due to the presence of the hydrophobic alkyl chain of the esters.…”
Section: Resultsmentioning
confidence: 99%
“…Recentemente outros estudos também apontam a ação antimicrobiana do ácido linoléico sobre Candida albicans resistente ao fluconazol, Staphylococcus aureus (Kim, et al, 2020) e Escherichia coli (Jumina, et al, 2019). Pesquisadores afirmam que o ácido linoléico inibe a formação de biofilmes, impedindo a infecção (Kim, et al, 2020), inclusive, tendo seus efeitos antibacterianos comparado aos do antibiótico gentamicina, ao ser testado sobre bactérias Gram-negativas e Gram positivas em um estudo realizado na Arábia Saudita (Hichri, et al, 2019).…”
Section: Discussionunclassified
“…Monolaurin, monocaprin, monomiristine, monopalmitin, and monostearin are saturated monoglycerides in the form of solid [7][8][9][10]. On the other hand, if the -R groups are from unsaturated fatty acid, it could generate unsaturated monoglycerides such as monoolein and monolinolein that are tend to be in the form of thick liquid [11].…”
Section: Chemical Structure and Classification Of Monoglyceridesmentioning
confidence: 99%
“…Some studies have reported that monoglycerides are promising antibacterial, antifungal, and antiviral agents [2,9,11,18]. Medium-chain monoglycerides are revealed to have better antimicrobial activity than long-chain monoglycerides.…”
Section: Physicochemical Properties and Applications Of Monoglyceridesmentioning
confidence: 99%